(untitled) (Cadernos de Ética e Filosofia Política, 2015)
This paper aims to point up some trends presented by Marcuse’s One-dimensional Man, insofar as the theme of truth in Hegelianism helps to explain questions concerning temporality and historicity. Characterized as a phobic relation as well as a relation saturated with tensions and marked by irresolution, the temporality that lies on industrial society prepares the decisive occasion for an effective desalienation of consciousness, especially when Marcuse interrogates the link between the field historically occupied by aesthetic materials and the field of political emancipation. Then, we are outlining some considerations between these two fields: on the one hand, opposing these passages to Gerard Lebrun’s essay published in 1979 in memoriam to Herbert Marcuse; on the other hand, showing the problem of suspension of the Terror of State, according to Marcuse’s sentences as well as to aphorisms, which Hegel wrote on the eve of his elaboration of Phenomenology of Spirit. Since such exigency of suspension is inseparable from a wider form of rationality as well as this rationality is close to a utopia of concrete society, Hegel’s ethical State would be located at the beginnings of a political overcoming from the fear from death.